Numerical simulation of urban berthing quays in a dense housing (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Calculation of pile quay gantry type as a frame with rigid crossbarand a rigid beam, is a special case of the decision method, presented by N. Gersevanov. This method was widely used in the technical literature and regulatory documents. Translation of manual calculation on the computer almost retained the existing design scheme.Practical implementation of the engineering universal method offered early to calculation of mooring embankments in relation to a thin wall, is given by anchored inclined piles. In the calculation scheme bottom sealing is not used, and entered stiffness characteristics of the soil, clarifying the nature of the work structure.The obtained simplified solution determines the lateral pressure in the silo variable width. Engineering calculations showed that pressure is redistributed on the sheet pilling wall and  the inclined piles  from external soil pressure.Comparative calculations, taking into account the deformation characteristics of the soil showed a significant impact on efforts in the elements of the embankment compared to method N. Gersevanov.